Impact of Minority Races on Clinical Trials on Latency Antibiotics [12C]. (May 2020) - Bailey, Josianne; Davis-Nelson, Shareece; Martin, Courtney; Mason, Danielle; Yao, Ruofan; Chan, Elena
Abstract : INTRODUCTION: Racial variations in response to therapy exist in many areas of medicine, as it must in obstetric practice. The objective of this study was to determine if the study populations in published literature on latency antibiotics (LA) in the treatment of preterm premature rupture of membrane (PPROM) were diverse enough to demonstrate a benefit for minority races. METHODS: This was a meta-analysis of literature published between 1995 and 2018 by searching PubMed using the keywords: antibiotics, preterm and ruptured membranes. Included studies were randomized clinical trials that identified the racial composition and delivery within 48 hours as an outcome of interest. Population level modeling was performed on the pooled result by recalculating the rate of outcome for each study if the rate of outcome of a particular race was the same between intervention and placebo arms. Pooled results that remain statistically significant after race specific adjustments suggest minimal influence from that particular race. RESULTS: There were 495 studies identified, 64 of which were clinical trials. Three studies reported racial composition of the study population and were included in the analysis. LA decreased risk of delivery within 24hrs (RR 0.80, 95% CI [0.67–0.94]). Race adjusted pooled result remained significant for white (RR 0.82, 95% CI [0.70–0.97]), black (RR 0.80, 95% CI [0.67–0.94]), Hispanic (RR 0.81, 95% CI [0.69–0.96]) and Asian (RR 0.79, 95% CI [0.67–0.93]). CONCLUSION: In studies on latency antibiotic use in PPROM, no individual race had a major influence on the pooled result based on studies that published population racial composition.